ACTIVISM : Documents of Contemporary Art - Dias Ramos, Alfonso; Snow, Tom (London : Whitechapel Gallery, 2023)
Artists surveyed include : Abbas, Basel & Abou-Rahme, Ruanne ; Al-Badri, Nora ; Allora & Calzadilla ; Ashford, Doug ; Baca, Judith ; Bauer, Ute Meta ; Beech, Dave ; Berardi, Franco 'Bifo' ; Bruguera, Tania ; Brunner, Christoph ; Butler, Judith ; Cabral, Amílcar et al.
Artists have consistently engaged in activist discourse, lending their skills to social movements, and regularly participating in civil and social rights campaigns while also boycotting cultural institutions and exerting significant pressure on them. From ACT UP and its affiliate groups since the dawn of the AIDS crisis to the counter-spectacle and street theatrics of the Arab Spring and Occupy, to ongoing protest movements such as Black Lives Matter, Rhodes Must Fall, and Decolonize This Place, activist aesthetics has proven increasingly difficult to define under traditional classifications.(from publisher)
boek